2002
DOI: 10.1002/glia.10099
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of intracellular ascorbate from dehydroascorbic acid by astrocytes is decreased after oxidative stress and restored by propofol

Abstract: Primary rat astrocyte cultures absorbed dehydroascorbic acid from the medium and reduced it to intracellular ascorbate. Uptake of dehydroascorbic acid (5-200 microM) was inhibited only partially by glucose (10 mM). The remaining glucose-insensitive component of dehydroascorbic acid uptake was inhibited reversibly by sulfinpyrazone (IC(50) = 80 microM). Dehydroascorbic acid uptake was not mediated by Na(+)-ascorbate cotransporters or volume-sensitive anion channels because it was neither Na(+)-dependent nor blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 38 publications
2
34
0
4
Order By: Relevance
“…5B). The observation that tBuOOH treatment depletes cellular ascorbate has been made previously in rat hepatocytes (44) and rat astrocytes (45). Altogether, our results indicate a correlation between the VTC2 mRNA levels and L-ascorbic acid content in C. reinhardtii cells exposed to oxidative stress.…”
Section: Vtc2 Transcript Levels and Ascorbate Levels Are Increased Insupporting
confidence: 88%
“…5B). The observation that tBuOOH treatment depletes cellular ascorbate has been made previously in rat hepatocytes (44) and rat astrocytes (45). Altogether, our results indicate a correlation between the VTC2 mRNA levels and L-ascorbic acid content in C. reinhardtii cells exposed to oxidative stress.…”
Section: Vtc2 Transcript Levels and Ascorbate Levels Are Increased Insupporting
confidence: 88%
“…22) In an environment in which cellular GSH is depleted, a profound reduction in the ability to reduce DHA to AA has been suggested to take place in some cells such as endothelial cells and erythrocytes. 23,24) Moreover, it has been reported that, in adult mice with GSH depletion, the levels of DHA in tissues increased markedly.…”
mentioning
confidence: 99%
“…However, today we know that astrocytes perform critical physiological activities, such as (1) the uptake of extracellular glutamate for recycling into glutamine to avoid neuronal excitotoxicity; (2) the release of lactate to be used by neurons for energy production; (3) the release of interleukin-6 (IL-6) and tumor growth factor-beta (TGF-beta) neuroprotective cytokines; (4) the synthesis of apolipoprotein E for axonal growth; and (5) the release of trophic factors, such as nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and ciliary neurotrophic factor (CNTF), among others [40]. Moreover, astrocytes are required for vitamin C recycling in the CNS due to their ability to uptake DHA from the extracellular space and, in virtue of its elevated reducing power, to efficiently reduce it back into AA [41,42]. After that, astrocytes release AA to the extracellular space to maintain stable AA concentrations [43].…”
Section: Vitamin C Recycling Between Astrocytes and Neuronsmentioning
confidence: 99%